Glaciological and geomorphological map of Glacier Noir and Glacier Blanc, French Alps. Issue 3 (26th May 2016) - Lardeux, Pierre; Glasser, Neil; Holt, Tom; Hubbard, Bryn
Abstract : This paper presents and describes a glaciological and geomorphological map of Glacier Noir and Glacier Blanc, French Alps. Glacier Noir is a debris-covered glacier and is adjacent to Glacier Blanc, a clean-ice (debris-free) glacier. The glaciological and geomorphological evolution of Glacier Blanc is well known, but the evolution of Glacier Noir is poorly understood, as is the case for many debris-covered glaciers globally, despite their importance in a number of mountain ranges around the world (e.g. European and Southern Alps, the Himalayas and the Rockies). The accompanying map was created by manually digitising aerial ortho-images and historical georeferenced photographs from 1952 to 2013. The main glacial and geomorphological features of both glaciers were mapped, including debris cover, crevasses, moraines, hummocky terrain and scree areas. Hydrological features (supra- and pro-glacial streams and meltwater ponds) were also mapped. The map illustrates the key differences between Glacier Noir and Glacier Blanc, and is important for understanding future glaciological and geomorphological changes.